Fusariosis in rubber tree: pathogenic, morphological, and molecular characterization of the causal agent - Pizetta, Marília [UNESP]; Pierozzi, Caroline Geraldi [UNESP]; Ayukawa, Yu; Kashiwa, Takeshi; Komatsu, Ken; Teraoka, Tohru; Arie, Tsutomu; Furtado, Edson Luiz [UNESP] (Springer Nature, 2021)
Fusariosis, one of the phytosanitary problems found in rubber producing areas in the northwest of the state of São Paulo, is a disease that affects the bark of the adult plants, affecting the exploitation of latex. The typical symptoms appear as cracks in the bark that expand from the rootstock towards the tapping panel, causing a drying of the latex flux in the injured region, impeding latex tapping. Due to the recent incidence of this disease in rubber plantations, the goal of this study was to characterize the Fusarium associated with symptomatic rubber tissue in three different locations in the state of São Paulo. In order to identify Fusarium species, pathogenicity, morphological, cultural and molecular studies were carried out. A total of 51 isolates were obtained and separated into three groups based on macroconidium morphology, presence or absence of sporodochia, types of chlamydospores, formation of phialides and conidiogenesis of microconidia and mesoconidia, mycelial growth rate and coloring of the colonies. These groups were corroborated using DNA sequence information for five different genetic loci, and were subsequently recognized as Fusarium oxysporum, F. incarnatum and F. decemcellulare. Our results further showed that all 51 of the Fusarium isolates recovered were pathogenic to rubber tree seedlings of RRIM 600 standard clone. This study also reports for the presence of F. oxysporum and F. incarnatum in rubber plantations in the state of São Paulo and in Brazil.
Keywords: Fusarium spp; Phylogenetic and taxonomic studies on fusarium; Rubber cultivation; Tapping panel disease